The Effect of Storage Duration and Invigoration Treatment on Viability of Cocoa (Theobroma cacao L.) Seeds - Tri Widiyanti; Agus Miftakhurrohmat (Nabatia, 2016)
The aim of this study was to determine the effect of giberrelin (GA3) storage durationand treatment on the viability of cocoa (Theobroma cacao L.) seeds carried out at theLaboratory of Indonesian Center for Seedling and Plant Protection (BBPPTP) Surabayaon Mojoagung No. No. 52, Mojoagung Subdistrict, Jombang Regency in February toApril 2014. This study used a completely randomized design with factorial patterns with2 factors. The first factor is the storage time which consists of 4 stages P1 (7 days ofnatural storage of seeds), P2 (14 days of storage of natural seeds), P3 (22 days of storageof natural seeds), and P4 (29 days of storage of natural seeds). The second factor isinvigoration treatment which consists of 3 types without treatment (I0), GA3 10 ppm(I1), GA3 20 ppm (I2). The results showed a significant interaction between storage timeand invigoration treatment of plant height and germination capacity, storage durationtreatment affected the variable number of leaves, 7 days storage time (P1) produced theaverage number of leaves (3.75 strands) even though the result is the same as the storageperiod of 14 days (P2). While the invigoration treatment had no effect on the observationvariable of the number of leaves.